THE SOCIAL REALITY OF WOMEN'S LIVES AS REPRESENTED IN THE MOVIE OF BARBIE (2023) - Husna, Dwi (Faculty of Letters Universitas Balikpapan, 2024)
Women have historically been depicted through negative stereotypes, portrayed as dependent, vulnerable, and unable to lead. Films often reinforce these roles, emphasizing women's domestic responsibilities while men dominate public spheres. However, the release of Barbie (2023) presents a transformative perspective, advocating for gender equality. This study analyzes the representation of women in Barbie (2023) using Roland Barthes' semiotic theory, focusing on signs, myths, and their connotative and denotative meanings. The research uncovers three key representations: (1) women can achieve any aspiration; (2) women can be independent and assertive; and (3) women exhibit courage in the face of oppression. The findings reveal that the protagonist in Barbie reflects the evolving social realities of women, depicting them as strong and independent, contrary to traditional patriarchal views. This shift indicates a progressive decline in outdated gender perspectives, showcasing a positive portrayal of gender equality. Ultimately, Barbie (2023) serves as a significant cultural artifact that promotes a more equitable view of women's roles in society.